Telegram (copy) - Hallsworth, Joseph; Tewson, Vincent
012a-0013-001 23-11-38 4.45 PM CBerks. Rt. Hon. Neville Chamberlain, c/o British Embassy, PARIS. General Council of Trades Union Congress meeting to-day gravely disturbed by reports suggesting possible granting of belligerent rights to Spanish rebels stop Council protests most strongly against any such step as certain to arouse deepest concern and hostility of Trade Unionists and others stop Would also lead to more dangerous disunity in the democracies and involve starvation of the Spanish people stop Council urges you not to involve this country in being party to such a grave injustice HALLSWORTH, Chairman. TEWSON, Assistant Secretary. 292/946/12a/13